INTEGRASI SERVQUAL DAN SIX SIGMA UNTUK PENINGKATAN KUALITAS LAYANAN PELANGGAN UKM PRODUK KERAJINAN KABUPATEN REMBANG - Agustina Widodo; Muhammad Zaky Wahyuddin Azizi (STIE Pelita Nusantara Semarang, 2020)
The SME (small medium enterprise) sector has a sufficient role, the quality of service is now an important priority for businessman in understanding the needs and desires their customers. Comparison of quality can be seen from the difference between the assessment of business management with the assessment of customers, then the concept of six sigma are DMAIC (define, measure, analyze, improve and control) is the structured methodology used to reduce the level of error in providing services to customers. There are a number of problems faced by dewan kerajinan nasional daerah (dekranasda) SME’s: business management is still very simple, the average human resource has a low level of education, does not have a good ability to market the products produced, financial limitations, limited access to raw materials and limited technology. The analysis results obtained that there are 5 complaints that most complained by consumers are less strategic location, lack of attention to individual customers, brochures and service facilities are inadequate, service is still long and the lack of waiting room facilities. the planned improvement that will be carried out is to improve services by using technology facilities, improve the quality of customer waiting room services, structuring the availability of brochures and information.